Analyzing the Impact of Population Density on Hepatitis A Prevalence Using Geographic Information Systems (GIS) in Sudimoro District, Pacitan Regency - Nurdiansyah, Robbi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This study examines the relationship between population density and Hepatitis A prevalence in Sudimoro District, Pacitan Regency, using data from 2019. Geographic Information Systems (GIS) technology was employed to analyze spatial patterns and correlations. Method: The research applied a quantitative approach, utilizing secondary data on Hepatitis A cases and population density. Simple linear correlation analysis revealed a moderate positive correlation (r = 0.48) between population density and the number of Hepatitis A cases, indicating that higher population density is associated with increased disease prevalence. Findings: Villages with high density, such as Gunung Rejo and Sudimoro, generally reported more cases, while those with lower density showed fewer cases. However, anomalies like Sembowo, which has high density but fewer cases, suggest that other local factors, such as sanitation and healthcare access, also play significant roles. The study underscores the importance of targeting high-density areas for public health interventions while considering additional factors influencing disease spread. Further research is recommended to explore these variables in more detail.